Treatment for cutaneous arteritis patients with mononeuritis multiplex and elevated C‐reactive protein. Issue 12 (4th December 2013) - Kawakami, Tamihiro; Okudaira, Azusa; Okano, Tatsuro; Takeuchi, Sora; Kimura, Satoko; Soma, Yoshinao; Ishizu, Akihiro; Arimura, Yoshihiro; Kobayashi, Shigeto; Ozaki, Shoichi
Abstract Cutaneous arteritis (cutaneous polyarteritis nodosa, CA) is a necrotizing vasculitis of arteries within the skin. CA is a new classification under single‐organ vasculitis, as adopted by the 2012 Chapel Hill consensus conference (CHCC 2012). Some patients originally diagnosed as having CA could develop additional disease manifestations that warrant reclassifying as systemic polyarteritis nodosa (PAN) according to the CHCC 2012. We retrospectively investigated 101 patients with CA seen at our department between 2003 and 2012. There was a significantly higher frequency of inflammatory plaques and leg edema in CA patients with elevated C‐reactive protein (CRP) compared to CA patients with normal CRP. Similarly, there were significant differences in the incidence of arthralgia and mononeuritis multiplex between the two patient groups. We found significantly positive correlations between CRP and creatinine titers in serum in all 101 CA patients. Prednisolone was administrated in a significantly greater percentage of patients with elevated CRP compared to patients with normal CRP. Repeated i.v. cyclophosphamide pulse therapy (IV‐CY) with prednisolone therapy at an early stage resulted in complete resolution without adverse effects or severe complications. We regard inflammatory plaques and leg edema with elevated serum CRP as an indication of a more severe condition, and treated them effectively with prednisolone. Assuming mononeuritis multiplex and/or arthritis exist with elevated CRP, we propose that earlier treatment by IV‐CY with prednisolone should be indicated for CA patients who demonstrate these more severe manifestations to prevent progression to PAN.